Studies on the Thrombogenic Activities in Two Prothrombin Complex Concentrates - Hedner, Ulla; Nilsson, Inga Marie; Bergentz, Sven-Erik (Thrombosis and Haemostasis, 1979)
The effect on the coagulation and fibrinolytic systems of various factor IX concentrates after addition of heparin, antithrombin III or Trasylol to the concentrate before infusion into dogs was studied in an attempt to characterize the clot-promoting activity or activities in these concentrates. After infusion of Preconativ (AB Kabi; 100 u factor IX/kg bodyweight) only small decreases of fibrinogen and platelet count in the samples taken 1 and 4 hrs after infusion were found. Addition of heparin (10 u/ml; 5 dogs) or Trasylol (40 u/u factor IX initially followed by 10,000 u/h; 3 dogs) had no effect but addition of antithrombin III (100 u/kg; 3 dogs) prevented all changes. Infusion of Konyne (Cutter Laboratories; 100 u/kg bodyweight) induced marked decreases of both fibrinogen and the platelet count at 1, 4 and 24 hrs after infusion and the ethanol gelation test became positive. Addition of heparin (10 u/ml; 5 dogs) diminished the changes but did not completely counteract them. Antithrombin III (100 u/kg; 3 dogs) added to the concentrate before infusion also reduced the induced changes to about the same extent as heparin. Trasylol (40 u/u factor IX initially followed by 10,000 u/h; 3 dogs) did not seem to have any effect. Addition of both antithrombin III and Trasylol (4 dogs) did, however, prevent almost all changes.It is thus obvious that the two commercial factor IX concentrates used may contain clot promoting activities and that these activities may differ between various concentrates.